STRATIGRAPHY, PROVENANCE, TIMING AND CONTROL OF INCISED VALLEYS IN THE FERRON SANDSTONE - Kynaston, David A. (My University, 2019)
This thesis evaluates the nature, provenance, geometry and morphology of incised valley fills to test assumptions made by valley models using ancient examples from well exposed outcrops, in the late Turonian Ferron Sandstone Member of the Mancos Shale Formation in southeastern Utah. The relevance of this work will have particular significance to long wavelength cycles of fluvial landscapes and valley morphology, non-marine reservoir characterization and significant implications for non-marine response to high frequency allogenic cycles such as climate change and changes in relative sea-level. This study illustrates the stratigraphic complexity of valley fill deposits at three levels of spatial resolution. At channel scale within the lower backwater, facies architecture and paleohydraulic analysis are used to predict the degree of shale drape coverage of point bars in a tidally-influenced incised channel. At channel belt scale the study documents a tidally incised, mudstone prone trunk-tributary valley fill and overlying highstand fluvial succession within a stratigraphic framework of fluvial aggragation cycles. 3D photogrammetry models and a high resolution GPS survey are used to restore the morphology of a trunk-tributary valley floor, revealing a surface of tidal ravinement and tidal drainage morphology. At a regional scale, this study radically revises the paleogeographic mapping of the Ferron trunk system, spanning over 1,600 km2. Provenance analysis reveals Ferron Notom trunk valleys were filled at times by sediment from the Mogollon Highlands of Arizona to the southwest, and alternately by sediment from the Sevier Thrust Front to the northwest. Evidence shows the Ferron trunk rivers, previously hypothesized to be an avulsive axial drainage, to be more analogous to Quaternary examples.
INCISED VALLEYS IN THE FERRON SANDSTONE
Keywords: incised valleys; backwater; tributary valleys; detrital zircons; paleogeography; Turonian; Ferron Sandstone; Notom Delta